Pengaruh Kesiapan Belajar Online dan Motivasi Belajar Terhadap Aktivitas Belajar Mahasiswa Baru Program Studi Manajemen Dakwah - Abdullah Syifa (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: This research was conducted to prove that online learning readiness and learning motivation have an effect on student learning activities of the IAIN Pontianak IAIN Management Dakwah Program Study. This study uses a quantitative approach. The independent variable in this study is online learning readiness and learning motivation, while the dependent variable is the learning activities of new students. The sampling technique used was total sampling. Data were collected using a questionnaire. The classical assumption test uses the normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test. The data that has been collected from the questionnaire is then analyzed using multiple linear regression tests. The hypothesis compiled by the researcher is that there is an effect of online learning readiness and learning motivation simultaneously on the learning activities of new students. The conclusion of this study is that online learning readiness and learning motivation simultaneously have a significant effect on new student learning activities with a significant value of 0.00 (0.000 <0.05). The effect is simultaneously affected through the coefficient of determination (R square) of 0.738 or 73.8%. This means that the variables readiness and motivation to learn simultaneously have an effect of 73.8%.